TALKING STICK MODEL ON NONFORMAL EDUCATION - Rahmat, Abdul (LPM Penalaran UNM, 2017)
AbstractOne effort to improve the ability of learner to pronounce alphabet is through talking stick model. It was a classroom action research based on preparation of learning which reflected the steps that must be done by the teacher. The procedure consisted of two cycles and each cycle consisted of two meetings. Based on the data obtained from the implementation of action cycle II showed that the number of package C learner that can afford is 18 or 86% learners, while the number of learner who could not afford about 3 people or 14 %. Thus the learning of the 100% talking stick model has been successful in accordance with the predefined performance indicators by the researcher. The results caused by the maximization and effectiveness of the application of the talking stick model on learning English, especially English alphabet pronunciation.Keywords: Classroom action research, Learning, Talking stickAbstrakSalah satu upaya untuk meningkatkan kemampuan warga belajar untuk mengucapkan alfabet adalah melalui model talking stick. Penelitian ini adalah penelitian tindakan kelas berdasarkan persiapan pembelajaran yang mencerminkan langkah-langkah yang harus dilakukan oleh pamong belajar. Prosedur terdiri dari dua siklus dan setiap siklus terdiri dari dua pertemuan. Berdasarkan data yang diperoleh dari pelaksanaan tindakan siklus II menunjukkan bahwa jumlah warga belajar Paket C yang mampu adalah 18 warga belajar atau 86%, sedangkan jumlah warga belajar yang tidak mampu sekitar 3 orang atau 14%. Dengan demikian pembelajaran model talking stick 100% telah berhasil sesuai dengan indikator kinerja yang telah ditetapkan oleh peneliti. Hasil tersebut disebabkan oleh maksimalisasi dan efektifitas penerapan model talking stick pada pembelajaran bahasa Inggris, khususnya pengucapan alfabet bahasa inggris. Kata Kunci: Penelitian tindakan kelas, Pembelajaran, Model talking stick